A multi-stage optimization of pedestrian level wind environment and thermal comfort with lift-up design in ideal urban canyons. (April 2019) - Du, Yaxing; Mak, Cheuk Ming; Li, Yantong
Highlights: A multi-stage optimization method is proposed for building design in ideal urban canyons. The pedestrian level wind environment and outdoor thermal comfort is selected as optimization objectives. The combination of CFD simulation and RSM approach is used to develop surrogate models. The NSGA-II algorithm is applied to find the Pareto optimal solutions. The findings are helpful in building a sustainable urban environment. Abstract: Improvements for the pedestrian level wind environment and outdoor thermal comfort have become increasingly important in urban planning in light of concerns about global warming and urban heat island effects. Therefore, the goal of this study is to determine the optimum wind environment and outdoor thermal comfort for an ideal urban canyon in which the buildings have lift-up designs. A multi-stage optimization method is proposed consisting of three stages for the optimization process, e.g., surrogate model development, multi-objective optimization, and decision-making. An area weighted wind velocity parameter ( M V R ¯ ) and an outdoor thermal comfort parameter ( P E T ¯ ) are chosen as the design objectives, and four design variables are selected. The response surface methodology combining computational fluid dynamics simulation results are used to fit surrogate models. The non-dominated sorting genetic algorithm is employed to find Pareto optimal solutions, and three decision-making strategies are adopted to determine the final optimum design solution in parallel. The optimization process of the ideal urban canyon confirms that the proposed method is highly effective to determine optimum building design in urban areas. The findings in this study are valuable for city-planners and policy-makers to build a sustainable urban living environment.